An experimental research on reinforced concrete deep beams fully wrapped with fiber reinforced polymers against shear - Akkaya, Hasan Cem; Aydemir, Cem; Arslan, Guray (ELSEVIER, 2022)
This paper presents a comprehensive experimental study to investigate the shear behavior of reinforced concrete (RC) deep beams fully wrapped with fiber reinforced polymer (FRP) strips. A total of eighteen deep beams were tested and the test results were evaluated. The test parameters were the shear span-to-effective depth ratio, the number of FRP layers, the clear spacing of FRP strips and the type of FRP. According to the experimental results, as the shear span-to-effective depth ratio increased, the rate of increase in the shear capacity decreased. On the other hand, the rate of increase in the deflection capacity increased with the shear span-to-effective depth ratio. It was observed that the steel plates used at the supports and loading point affected the contribution of FRP strips and the shear behavior of beams. Moreover, increasing the number of FRP layers, reducing the clear spacing of FRP strips or using glass FRP strips enhanced the shear and deflection capacities of beams. A comparative study was also conducted based on the experimental results. Comparisons between the experimental results of this study and the predictions obtained from a total of twelve models consisting of those given by the codes and those proposed by various researchers. The model superior to the others statistically is the one proposed by the German code.
Keywords: Deep beams; Shear behavior; Fiber reinforced polymer; Fully wrapped; The shear span-depth ratio; Carbon; RC BEAMS; T-BEAMS; BEHAVIOR; PERFORMANCE; CAPACITY; STRENGTH; DESIGN; STEEL; Construction & Building Technology; Engineering; Materials Science